2018
DOI: 10.1162/jocn_a_01226
|View full text |Cite
|
Sign up to set email alerts
|

Control Changes the Way We Look at the World

Abstract: The feeling of control is a fundamental aspect of human experience and accompanies our voluntary actions all the time. However, how the sense of control interacts with wider perception, cognition, and behavior remains poorly understood. This study focused on how controlling an external object influences the allocation of attention. Experiment 1 examined attention to an object that is under a different level of control from the others. Participants searched for a target among multiple distractors on screen. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 57 publications
4
40
0
Order By: Relevance
“…One promising option in this regard is behavioral paradigms that assess agency by modulating the extent to which participants’ can control moving stimuli with cursor movements [30, 31]. For example, in one experiment, Wen et al, 2018 [30] had participants identify a target circle among a group of distractors, while the trajectories of the two types of stimuli were influenced by the participants’ mouse movements to varying degrees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One promising option in this regard is behavioral paradigms that assess agency by modulating the extent to which participants’ can control moving stimuli with cursor movements [30, 31]. For example, in one experiment, Wen et al, 2018 [30] had participants identify a target circle among a group of distractors, while the trajectories of the two types of stimuli were influenced by the participants’ mouse movements to varying degrees.…”
Section: Introductionmentioning
confidence: 99%
“…One promising option in this regard is behavioral paradigms that assess agency by modulating the extent to which participants’ can control moving stimuli with cursor movements [30, 31]. For example, in one experiment, Wen et al, 2018 [30] had participants identify a target circle among a group of distractors, while the trajectories of the two types of stimuli were influenced by the participants’ mouse movements to varying degrees. Such tasks involve more extensive sensorimotor interaction from participants, and do not rely on the types of discrete timing judgments, like those used in the Libet clock paradigm [12], that have been criticized for susceptibility to memory confounds.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a recent study on the sense of control also reported that initial exploration of control greatly influences the detection sensitivity of changes in the subsequent sensing of control ( Wen et al, 2020 ). Moreover, previous studies reported both that lack of control is salient ( Blakemore et al, 1998 ; Timm et al, 2014 ) and that control captures attention ( Salomon et al, 2013 ; Wen and Haggard, 2018 ). Here, categorical perception of control presents a framework for understanding these phenomena; suggesting that differences in control potentially cause determinant changes in the control category is significant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research in cognitive science showed that the sense of agency greatly influences attention allocation. People efficiently monitor events that are relevant to themselves (i.e., under their control), but do not pay much attention to events that are out of their control (Wen and Haggard, 2018). In the case of driving a car, if people have a sense of agency over the car, their monitoring of the car and dynamic changes in the environment would be more sensitive and efficient.…”
Section: Sense Of Agency In Automationmentioning
confidence: 99%